Arithmetic divisors on orthogonal and unitary shimura varieties - Bruinier, Jan H & et al. (Paris: Societe Mathematique De France, 2020)
The three papers in this volume concern the modularity of generating series of divisors on integral models of orthogonal and unitary Shimura varieties
Modularity of generating series of divisors on unitary Shimura varieties -- Arithmetic of Borcherds products
Includes bibliographical references
Keywords: Algebraic Geometry; Arithmetic Intersection Theory; Borcherds Products; Shimura Varieties